Urban planners' efforts in resolving conflict between two forces: growth and conservation - Zainal Abidin, Shahrum; Asmawi, M. Zainora; Abdullahi, Hashim; Rasool, Ako Mustafa; Mohamed Sellu, Gajikoh; Mohd Nasir, Nadia; Abdul Aziz, Maimunah; Ismail, Fatin Liana; Ibrahim, Mansor (2012)
Urban and regional planning has the following major objectives: Promotion of accessibility, the use of resources as wisely as possible, separation of conflicting land uses, preventions of slum development, upgrading of settlements and environmental pollution control (Dantudu ,1998).The paper highlights the major difference between two urban planners conflicting interests of growth and conservation. The research states the factors influencing growth and related factors attached to conservation. Furthermore, major planning policies such planning development guideline, environmental protection act, town planning act, mix land use approach and land use planning approach elaborated in achieving conservation and the extent of planners current interest in sustainable development. Finally, Malaysian urban planners for harmonizing the contradicting forces,efforts in conserving the environment and in achieving sustainable development are explained.